FES204 : Pattern construction and manipulation / College of Creative Arts - UiTM, College of Creative Arts (Universiti Teknologi MARA (UiTM), 2022)
This subject provides the student with knowledge of the standard industrial techniques used in the construction of garments. Students will learn the manipulation methods using basic bodice blocks to produce various design lines. All the projects are produced base on a carefully progression of difficulty including manipulation techniques, fitting problems, complicated construction methods and fabric handling.